« Nos a Gulielmo victi... » ou histoire, linguistique et idéologie - Christophe Bord (Anglophonia)
In English-speaking countries, particularly in Britain, linguistic historiography as applied to English often seems dominated by rather unscientific sentiments of a nationalistic nature and does not hesitate to go to great lengths to negate the loss of the Germanic character of the language. To achieve this goal it rather systematically adopts four main strategies: besides overemphasizing the importance of function words in the English lexicon, it ignores the Celtic substratum and downplays the different varieties of the French superstratum, while boosting the Old Norse adstratum for purely historical reasons of Germanic relatedness. In this article we try to give an idea of the dimension of the phenomenon and attempt to scrutinize the issue of Anglo-Norse linguistic relationships where much, it seems to us, is taken for granted, but little demonstration of any real significance has thus far been delivered.